Predictive Value of Neutrophil-Lymphocyte Ratio for Long-Term Cardiovascular Event Following Coronary Artery Bypass Grafting - Gurbuz,Orcun (2020)
Abstract Objective: To investigate the predictive value of preoperative neutrophil-lymphocyte ratio (NLR) for long-term major adverse cardiac and cerebrovascular events (MACCE), which have not yet been well described, in patients undergoing coronary artery bypass grafting (CABG). Methods: The records of 751 consecutive patients who underwent elective CABG between January 2008 and January 2010 were retrospectively enrolled and stratified according to quartiles of preoperative NLR. At 7.8-year follow-up, MACCE was considered as an endpoint. Results: Overall MACCE was 11.6% of all cases. Long-term myocardial infarction, percutaneous coronary intervention, stroke and cardiovascular mortality were found associated with the upper NLR quartile (P<0.001, P<0.001, P=0.005, P<0.001, respectively). In multivariate analysis, NLR on admission remained an independent predictor of long-term MACCE (OR 1.087, 95% CI 1.026-1.151; P=0.004), in all EuroSCORE risk groups (P<0.001; P<0.001; P=0.029). The receiver operating characteristic (ROC) curve analyses revealed an NLR cut-off value of 4.32 predicting MACCE. Conclusion: NLR is a useful and readily available predictive marker of long-term MACCE following CABG, independent of the EuroSCORE.